IMPLEMENTING CHARACTER EDUCATION DURING THE COVID-19 PANDEMIC AT ELEMENTARY SCHOOL - Agustinus Tanggu Daga (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Character education during the Covid-19 pandemic underwent various changes, including character education at elementary schools. These changes affected the design of education as well as the character assessment and the roles of teachers and parents. The problem in this research was how to carry out character education in learning during the Covid-19 pandemic at elementary schools. This research found that teachers implemented character education in the learning process even though learning was conducted from home and prioritized by schools. Character education was needed by students who studied from home. Teachers carried out character assessments and adjusted them to the students’ conditions and the Covid-19 situation. The instilled character values were also adjusted to the students’ needs, such as religious values, and values relevant to the Covid-19 condition such as health, caring, tolerance, responsibility, hard work, and love of reading. Teachers utilized online learning media such as WhatsApp, videos, video calls, Zoom, and Google Forms. Finally, teachers and parents shared responsibilities in implementing character education in the learning process carried out from home.